An Analysis of how Customer Value, Service Innovation, and Brand Image Influence Chinese Online Travel Agency Customer Satisfaction and Loyalty - Sun, Lei; Chamsuk, Wawmayura; Saengnoree, Amnuay; Sornsaruht, Puris (My University, 2024)
This study examines the relationships between customer value (CV), service innovation (SI), OTA brand image (IM), e-customer satisfaction (ECS), and e-customer loyalty (ECL) in the online travel industry. From February to March 2023, the authors collected and analyzed opinions from 361 Chinese online travel agency (OTA) users via confirmatory factor analysis (CFA) and partial least squares structural equation modeling (PLS-SEM) with AMOS Version 22. SPSS for Windows Version 24 was employed for descriptive statistics. The analysis revealed positive direct effects of CV (0.45), SI (0.60), and IM (0.35) on ECS, highlighting their importance in shaping customer satisfaction. ECS also had a strong direct effect on ECL (0.75), emphasizing its role in driving loyalty. Additionally, CV and IM had indirect impacts on the ECL through the ECS (0.34 and 0.26, respectively). The model explains 82% of the variance in ECS and 89% in ECL. These findings offer strategic insights for OTAs, stressing the importance of enhancing CV, SI, and IM to improve ECS and ECL. The study discusses theoretical and practical implications, highlighting the importance of a customer-centric approach in the online travel industry.
Keywords: customer loyalty; customer satisfaction; customer value; online travel agency (OTA); service innovation; Thailand